2011
DOI: 10.1021/bm101233m
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive PEG-Anthracene Grafted Hyaluronan as a Controlled-Delivery Biomaterial

Abstract: Ophthalmic drug delivery to the posterior segment of the eye could benefit from a responsive controlled drug delivery system with light or laser inducible changes. For example, the delivery of age-related macular degeneration drugs requires invasive monthly injections making long-term photoresponsive drug delivery a desirable option. The feasibility of this may be facilitated by both the transparency of the eye and the advanced technology in ophthalmic lasers. Hyaluronic acid photogels that are compatible with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Compared with the diffusion of larger molecules in other types of hydrogels (i.e., 144 kDa IgG55 and 2 MDa dextran),23 diffusion of GFP still occurred several orders slower. Diffusion on a similar scale has recently been shown by Wells et al with slightly smaller lysozyme (14.4 kDa) in a photoresponsive PEG‐anthracene grafted hyaluronan hydrogel 56. Although the accuracy of the experimental data needs to be improved, effective immobilization of GFP was unambiguously demonstrated.…”
Section: Resultssupporting
confidence: 64%
“…Compared with the diffusion of larger molecules in other types of hydrogels (i.e., 144 kDa IgG55 and 2 MDa dextran),23 diffusion of GFP still occurred several orders slower. Diffusion on a similar scale has recently been shown by Wells et al with slightly smaller lysozyme (14.4 kDa) in a photoresponsive PEG‐anthracene grafted hyaluronan hydrogel 56. Although the accuracy of the experimental data needs to be improved, effective immobilization of GFP was unambiguously demonstrated.…”
Section: Resultssupporting
confidence: 64%
“…Anthracene and spiropyran have been reported as photodimerization groups in photo‐responsive hydrogels since they can reversibly dimerize and dedimerize under UV–vis light radiation. Sheardown and coworkers reported a photo‐responsive PEG‐anthracene grafted hyaluronan (HA) . After UV radiation, the synthesized PEG‐anthracene HA photogels exhibited quick and high model compound loading and extended release duration ( Figure 8 ).…”
Section: Ophthalmic Hydrogel Systemmentioning
confidence: 99%
“…Meanwhile, the eye is a very unique vital organ that is poorly accessible to drugs/therapeutics following systemic or local administration. It is reported that only less than 5% of topically administered drug enters the eye as a result of poor permeation and extensive drug loss do occur through various mechanisms such as lacrimation, tear dilution, and tear turnover [3, 4]. Achieving the desired therapeutic outcomes from topical drug administration may be further hampered by (a) poor patient adherence to daily medication dosing instructions; (b) difficulties in accurately administering drug to the eye; and (c) variable drug efficacy.…”
Section: Introductionmentioning
confidence: 99%